International Community and Indonesiaâs Policy Towards Climate Change Post-2012 - Afriansyah, Arie; Purwandaya, Andrea C. (Papua Law Journal, 2017)
Throughout the international climate change regimeâs development up until 2012, the emergence of new and helpful mechanisms and negotiation processes were often accompanied by setbacks such as withdrawals and unmet State obligation. The object of this study focused on international community and indonesiaâs policy towards climate change. The Method of this study is normative legal research. The result Â of this thesis is to situate the internal/domestic climate of several States (the U.S., Canada, Brazil, Norway, and Indonesia) and one regional organization (the EU); and connect it to the outward international policies each have chosen to put forward on the negotiation table and/or submit themselves to. Given the global nature of and concern about climate change, it feels as if there is no shortage of lessons to pick â from outright refusal to be legally bound to the regime at all (the U.S.), an unprecedented and recent move of formal and official withdrawal from the regimeâs key instrument (Canada), the struggles with implementation that a regional organization might face (the European Union), to the recent moves and measures in environmental protection pioneered and led by States characterized by their increasingly strong economies (Brazil, Norway, and Indonesia).